Pengaruh Pemberian Ibuprofen dan Paracetamol Terhadap Penurunan Nyeri Disminorhea di Pondok Pesantren X: The Effect of Giving Ibuprofen and Paracetamol on Reducing Dysminorhea Pain at X Islamic Boarding School - Isma Oktadiana (Indonesian Journal of Pharmacy and Natural Product, 2023)
Dysmenorhea is menstrual discomfort that women feel during menstruation, particularly if it started while they were teenagers. If this condition is not addressed, it will have an effect on these teenagers. The goal of this study was to ascertain whether giving young women between the ages of 12 and 17 years old Ibuprofen 200 mg and Paracetamol 500 mg as pharmacotherapy would have any effect on alleviating the discomfort associated with dysmenorrhea. This study's experimental data collection method used a one group pretest-post test design without a comparison group. The value that the respondent provided in the form of pretest and post-test with Wilcoxon test. Purposive sampling was used for the sample process, while chi-square was used for analysis. The results of the Wilcoxon test, which produced a significance value of 0.000<0.05, demonstrated that there was a therapeutic effect of using Paracetamol 500 mg and NSAIDs, it means that there is a difference in the intensity of menstrual pain felt by respondents before and after therapy. The conclusion of this study is a significant effect on the administration of ibuprofen and paracetamol on reducing the intensity of menstrual pain in teenagers at X Islamic Boarding School ABSTRAK Disminorhea merupakan nyeri menstruasi yang dialami oleh wanita pada masa menstruasi terutama yang sudah dialami pada usia remaja, dimana jika hal ini tidak terobati akan berdampak pada remaja tersebut. Tujuan penelitian ini adalah untuk mengetahui pengaruh farmakoterapi pemberian Ibuprofen 200 mg dan Paracetamol 500 mg terhadap penurunan nyeri disminorhea pada remaja putri usia 12-17 tahun. Â Metode pengambilan data dalam penelitian ini dilakukan secara eksperimental dengan rancangan one group pretest-post test tanpa kelompok pembanding. Pengaruh dari penelitian ini akan dilihat dari nilai pretest dan postest dengan uji Wilcoxon. Teknik pengambilan sampel dengan cara purposive sampling dan dianalisis menggunakan chi-square. Hasil penelitian menunjukan bahwa terdapat pengaruh terapi penggunaan obat Paracetamol 500 mg dan NSAID yaitu ibuprofen 200 mg sebelum dan sesudah terapi, yang dapat menurunkan disminorea pada remaja putri, dibuktikan dengan uji Wilcoxon yang menghasilkan nilai signifikansi 0,000 <0.05 artinya terdapat perbedaan intensitas nyeri menstruasi yang dirasakan responden saat sebelum terapi dan sesudah pemberian terapi. Kesimpulan penelitian ini adalah bahwa terdapat pengaruh signifikan pada pemberian ibuprofen dan parasetamol terhadap penurunan intensitas nyeri menstruasi pada remaja di Pondok Pesantren X.